The Australian issid planthopper genus Orinda Kirkaldy, 1907: New subgenera, new species, host plant and identification key (Hemiptera: Fulgoromorpha: Issidae) - Constant, Jérôme; Semeraro, Linda (European Journal of Taxonomy, 2023)
A new subgenus of Orinda Kirkaldy, 1907, Montorinda subgen. nov., is described to accommodate two new species from southeastern Queensland, O. (Montorinda) eungellana sp. nov. from Eungella National Park and O. (Montorinda) montana sp. nov. from Mount Walsh National Park. The new species are compared to the other species of the genus and a new subgenus Scapulorinda subgen. nov. is described to accommodate Orinda (Scapulorinda) scapularis (Jacobi, 1928), leaving a single species in the subgenus Orinda: O. (Orinda) lucindae (Kirkaldy, 1906). Illustrations of the male holotype, a female paratype and male genitalia are provided for both new species as well as habitus and wing of O. (Scapulorinda) scapularis (Jacobi, 1928), the most closely related species, for comparison. The type series of the O. (Montorinda) montana sp. nov. was collected on Grevillea whiteana Mc Gill. (Proteaceae). The genus Orinda is only recorded from Queensland and now contains four species.